Analysis Of The Character Of Karin In The Novel Maharku Surah Ar-Rahman By Ahliya Mujahidin: Gestalt Approach (Kurt Kofkka) - Dewi Fitriya; Safina Amalia Oktaviana Anwar (Penerbit Hellow Pustaka, 2024)
The novel